Findings from the 2021 Yearbook Section on Health Information Management - Bloomrosen, Meryl; Berner, Eta S.; Section Editors for the IMIA Yearbook Section on Health Information Management (Yearbook of Medical Informatics, 2021)
Objectives: To summarize the recent literature and research and present a selection of the best papers published in 2020 in the field of Health Information Management (HIM) and Health Informatics.Methods: A systematic review of the literature for the IMIA Yearbook HIM section was performed by the two section editors with the help of a medical librarian. We searched bibliographic databases for HIM-related papers using both MeSH headings and keywords in titles and abstracts. A shortlist of the fifteen best candidate papers was first selected by section editors before being peer-reviewed by independent external reviewers.Results: The three major themes of Health Information Exchange (transmitting, sharing, and accessing patient health-related data and information) (HIE), Data Quality, and Privacy and Security make up 80% of the fifteen papers, with individual papers on personal health records, information governance and the professionalism of the HIM field.Conclusions: Traditional HIM concerns about HIM practice and workforce as well as issues about the data in electronic health records (EHRs) including data quality, coding, health information exchange among entities within the healthcare systems and privacy and confidentiality continue to be a large part of the HIM research literature. Although there was little research applying these themes to pandemic concerns, HIM professionals have the expertise to make ccontributions to public health informatics research and this research would benefit from their involvement.
Keywords: Health information management; health information exchange; data quality; privacy and security; electronic health records; public health informatics